THE LEGAL REVIEW OF INTRACEREBRAL ARTERIAL HEPARIN FLUSHING MEDICAL PROCEDURE AS A NON-EVIDENCE BASED THERAPY - Sapan, Heber Bombang; Husain, Bahtiar; Rokhmat, Rokhmat; Makbul, Ahmad; Osman, Ahmed Kheir (UNISSULA, 2024)
The implementation of medical practice must follow service standards. The purpose of this study is to determine the quality of medical services based on scientific evidence. The research method used was normative juridical, the results of the study state that in efforts to improve the quality of medical services in Indonesia, the government had set health service standards as binding laws for health workers. However, these service standards are often not always implemented, so they have the potential to cause deviations that are detrimental to the community. Quality medical services based on scientific evidence are the main paradigm for quality medical services and community protection. Currently, there are still medical actions that are not based on scientific evidence, intracerebral arterial heparin flushing but have been widely applied and commercialized. intracerebral arterial heparin flushing is an action that is not based on strong scientific evidence so it is unethical. Therefore, legal protection is needed for the community from medical actions that are not based on scientific evidence. Medical personnel are advised to comply with service standards and carry out medical practices based on scientific evidence in carrying out their profession in order to avoid violating the law.